Diagnostic value of MRI for posttreatment surveillance of early-stage (I-II) glottic larynx cancer - Mose, Lucas; Korkmaz, Emre; Visini, Miranda; Giger, Roland; Schanne, Daniel Hendrik; Elicin, Olgun (Strahlentherapie und Onkologie, 2025)
There is no uniformity across various guidelines in defining the modality and frequency of the follow-up, particularly regarding radiological imaging. The objective is to assess the diagnostic performance of magnetic resonance imaging (MRI)-based posttreatment surveillance for early-stage (I-II) glottic squamous cell carcinoma of the larynx.
Gesehen am 12.02.2026